Exogenous selenium promotes the growth of salt-stressed tomato seedlings by regulating ionic homeostasis, activation energy allocation and CO2 assimilation - Zhang, Wenbo; He, Xiaoling; Chen, Xianjun; Han, Hongwei; Shen, Bingru; Diao, Ming; Liu, Hui-ying (Frontiers in Plant Science, 2023)
This study is aimed at investigatingthe effects of exogenous selenium (Se) on the ionic equilibrium and micro-domain distribution, state transitions between photosystem I (PSI) and photosystem II (PSII), and the photosynthetic carbon assimilation efficiency of tomato (Solanum lycopersicon L.) seedlings under the influence of salt stress. The application of 0.01 mmol•L-1 exogenous Se had no significant effects on the selective transport capacity of sodium (Na), potassium (K), calcium (Ca) and magnesium (Mg) from the roots to leaves under salt stress. It, however, significantly hindered the absorption of Na by the root system and leaves, increased the ratios of K/Na, Ca/Na and Mg/Na, and relieved the nonuniformity of micro-domain ionic distribution, thus, mitigating the ionic homeostasis imbalance and ion toxicity induced by salt stress. Additionally, the application of exogenous Se overcame stomatal limitation, regulated the state transitions between PSI and PSII, and enhanced the initial and overall activity of Rubisco as well as the activities of Rubisco activase (RCA) and fructose-1,6-bisphosphatase (FBPase). It also increased the levels of expression of nine relevant genes in Calvin cycle, which subsequently improved the concentration of photosynthetic substrates, balanced the distribution of activation energy between PSI and PSII, promoted the efficiency of CO2 carboxylation and carbon assimilation, thereby increasing the photosynthetic efficiency of tomato seedling leaves under salt stress. Hence, the supply of exogenous Se can alleviate the inhibition of salt stress on tomato seedling growth by rebuilding ionic homeostasis and promoting photosynthetic capacity.